2020
DOI: 10.1074/jbc.ra119.011668
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli cellulose synthase subunit G (BcsG) is a Zn2+-dependent phosphoethanolamine transferase

Abstract: Bacterial biofilms are cellular communities that produce an adherent matrix. Exopolysaccharides are key structural components of this matrix and are required for the assembly and architecture of biofilms produced by a wide variety of microorganisms. The human bacterial pathogens Escherichia coli and Salmonella enterica produce a biofilm matrix composed primarily of the exopolysaccharide phosphoethanolamine (pEtN) cellulose. Once thought to be composed of only underivatized cellulose, the pEtN modification pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(70 citation statements)
references
References 40 publications
5
57
1
Order By: Relevance
“…At present, an understanding of the synthase responsible for bacterial cellulose biosynthesis has been largely limited to the study of Gram-negative model organisms. The Gram-negative bacterial cellulose synthesis (Bcs) complex is encoded by the bcsABCZ locus and represents the essential biosynthetic machinery required for production of the β-(1-4)-glucan polymer [16] that is subsequently derivatized by at least three distinct accessory cellulose modification systems described in Gram-negative bacteria [11,[17][18][19]. The proposed functions of the bcsABCZ gene products were largely inferred from structural and functional studies of other Gram-negative exopolysaccharide systems (e.g., the poly-β-(1-6)-N-acetyl-D-gluccoasmine (PNAG) biosynthetic system from Escherichia coli [20] and Staphylococcal species [21][22][23] or the alginate biosynthesis pathway from Pseudomonas aeruginosa [24]).…”
Section: Introductionmentioning
confidence: 99%
“…At present, an understanding of the synthase responsible for bacterial cellulose biosynthesis has been largely limited to the study of Gram-negative model organisms. The Gram-negative bacterial cellulose synthesis (Bcs) complex is encoded by the bcsABCZ locus and represents the essential biosynthetic machinery required for production of the β-(1-4)-glucan polymer [16] that is subsequently derivatized by at least three distinct accessory cellulose modification systems described in Gram-negative bacteria [11,[17][18][19]. The proposed functions of the bcsABCZ gene products were largely inferred from structural and functional studies of other Gram-negative exopolysaccharide systems (e.g., the poly-β-(1-6)-N-acetyl-D-gluccoasmine (PNAG) biosynthetic system from Escherichia coli [20] and Staphylococcal species [21][22][23] or the alginate biosynthesis pathway from Pseudomonas aeruginosa [24]).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose is a major component of biofilm matrix and may also act as an adhesion factor (El Hag et al, 2017). bcsA and bcsG genes are necessary to produce cellulose, and are involved in cell-cell aggregation and biofilm formation (Hu et al, 2015;Anderson et al, 2020). Our study suggested that LED may control the synthesis of cellulose and adhesion ability of C. Sakazakii cells by regulating the function of bcsA and bcsG, thus influencing the biofilm forming process.…”
Section: Discussionmentioning
confidence: 78%
“…[53,83,84] In addition, increased curli content in UTI89 pellicles yields a mechanically more robust film with increased elasticity. [73,85] The cellulosic component contributes to cohesive integrity of UTI89 pellicles, [12] and one recent study of BcsG indicated that pEtN modification does contribute to pellicle integrity in AR3110, although in different growth conditions at 30 C. [33] Thus, we sought to address the question of how pellicle formation in UTI89 and AR3110 might differ, knowing that the composition of the isolated ECM above revealed variation in the ratio of pEtN cellulose and curli. Then, we explored the influence of the pEtN modification in AR3110 and UTI89 pellicle formation and evaluated bcsA mutants.…”
Section: The Influence Of Phosphoethanolamine Cellulose and Unmodifmentioning
confidence: 99%
“…Recently, two groups reported crystal structures of the periplasmic C‐terminal domain of BcsG and confirmed its catalytic ability to remove pEtN from phospholipid head groups [ 18 ] and to add pEtN to a carbohydrate substrate. [ 33 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation